2019
DOI: 10.1111/liv.14207
|View full text |Cite
|
Sign up to set email alerts
|

Predicting HBsAg clearance in genotype A chronic hepatitis B using HBsAg epitope profiling: A biomarker for functional cure

Abstract: Background and Aim Functional cure is the major goal of chronic hepatitis B (CHB) therapy though few biomarkers predict this outcome. HBsAg epitope occupancy can be influenced by therapeutic and immune pressure. The aim of this study was to map the HBsAg epitope profiles during long‐term nucleos(t)ide analogue therapy in patients with genotype A CHB, in the context of HBsAg loss (SL)/seroconversion. Methods We evaluated 25 genotype A CHB patients in the GS‐US‐174‐0103 trial of HBeAg‐positive CHB patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Biomarkers for HBV functional cure include HBsAg clearance profile (CPs, defined by loss of binding at both loops 1 and 2 epitopes of the 'a' determinant)[ 15 ]. A 48th week and 192 nd week HBsAg CPs analysis of genotype A CHB patients on either tenofovir or adefovir for at least four years prior revealed its positive association with HBsAg loss (SL), seroconversion, and response to treatment[ 15 ].…”
Section: Advances In Treatment and Prevention Of Hepatitis Bmentioning
confidence: 99%
“…Biomarkers for HBV functional cure include HBsAg clearance profile (CPs, defined by loss of binding at both loops 1 and 2 epitopes of the 'a' determinant)[ 15 ]. A 48th week and 192 nd week HBsAg CPs analysis of genotype A CHB patients on either tenofovir or adefovir for at least four years prior revealed its positive association with HBsAg loss (SL), seroconversion, and response to treatment[ 15 ].…”
Section: Advances In Treatment and Prevention Of Hepatitis Bmentioning
confidence: 99%
“…Further support for the role of anti-HBs in HBV clearance comes from a study of individuals who cleared HBV infection during adefovir/tenofovir therapy. Using a 19-plex epitope mapping approach across the HBsAg antigenic 'a' determinant, occupancy of epitopes in loop 1 and loop 2 of the 'a' determinant was detected in those patients who went on to achieve a functional cure, suggesting that anti-HB responses across these regions are required for clearance [37].…”
Section: Role and Antiviral Function Of Anti-hbsmentioning
confidence: 99%
“…As introduced above, it has been suggested that anti-HBs could be depleted by the large number of circulating SVPs that greatly outnumber virions. In support of this suggestion is the finding that complexes of anti-HBs with circulating HBsAg are not recognized by current diagnostic assays, but can be detected in chronically infected patients using more highly sensitive immunoassays [37,38]. However, alternative explanations have been provided to understand this apparent lack of anti-HBs as an HBsAg-specific B-cell dysfunction.…”
Section: Hbsag-specific B-cell Dysfunctionmentioning
confidence: 99%
“…The S region contains the “a” determinant spanning from residues 99 to 160 and is thought to be the major anti-HBs epitope binding domain 11 . Antibodies targeting the “a” determinant have been reported to be potent neutralizers making them ideal candidates for testing as prophylactic or therapeutic reagents 12 .…”
Section: Introductionmentioning
confidence: 99%